Role of lactoferrin and its derived peptides in metabolic syndrome treatment - Zong, Xicui; Wang, Yajing; Chen, Yuqing; Fang, Penghua; Zhang, Yi (Frontiers in Endocrinology, 2025)
The prevalence of metabolic syndrome is increasing globally year by year, which has prompted researchers to actively seek and develop natural biotherapeutics to address this challenge. Lactoferrin (LF), as a multifunctional iron-binding natural transferrin, has garnered significant attention due to its potential role in regulating metabolism and the immune system. Recent studies show lactoferrin may influence lipid metabolism and glucose-insulin balance, and its levels are linked to body measurements. We systematically summarized the phenotypic and genotypic changes of LF in patients with metabolic syndrome, and the effect of exogenous LF on the treatment of metabolic syndrome. We also recapitulate LF can alleviate insulin resistance by inhibiting the NF-κB inflammatory pathway, activating the IRS/PI3K/Akt/Glut signaling pathway, and inhibiting the renin-angiotensin system to reduce the blood pressure, therefore improving the metabolic syndrome. This provides an important theoretical basis for the clinical application of LF in metabolic syndrome.